(untitled) (Global Journal of Human-Social Science, 2010)
The concept of eco-tourism in protected areas and their implications for the conservation of flora and fauna are of global significance. In north-west India, as most of the protected areas are surrounded by number of villages, therefore, the involvement of local communities in nature"s conservation is now-a-days widely acknowledged. Uttarakhand Himalaya in recent times harbours a good increase in ecotourism specially in protected areas (Biosphere Reserves, National Parks and Wildlife Sanctuaries) besides, efforts done by state government in building "tourism state" have promoted the tourism industry in general. This study aims at exploring the potential of eco-tourism in Rajaji National Park and the local people"s perceptions towards the local tourism, conservation of wildlife and substitutes for their livelihood. Additionally, study provides an out sketch of potential sites already developed or can be developed for increasing options for enhancing eco-tourism besides, providing information about various tools, which can attract the tourists from various disciplines. Many historical evidences are currently hidden inside the Rajaji National Park, which includes presence of antiquities at some places, tales of rehabilitated villages and efforts done by Britishers during early 20th century, should be explored and documented. Besides, jeep safari, elephant safari, if continued and bird watching are another key features present within the park. Famous temples of godess Mansadevi, Chandidevi and Sureshwaridevi are also situated in this forest stretch and currently Gujjar rehabilitation programme have had a prime impact on wildlife conservation, which can be involved in ecotourism coordination. Additionally, study has provided an outline for upliftment of tourism in adjoining protected areas and the management measures i.e. how to minimize the mananimal conflict with community participation and perceptions. Study suggested that the government should keep on emphasizing the wildlife conservation by taking into account the improvement of local people"s livelihood. This study provides an insight into understanding the eco-tourism potential in the Rajaji National Park and how they relate to wildlife conservation and mananimal conflict minimization. All of these findings may have wider implications for developing predictive models of mananimal interactions and also establishes a basis for decision-making in protected area management and in policy making specially for conflict-full protected areas.